DIAGNOSIS AND ACTIONS FOR LIQUIDATION OF DOGS STREPTOCOCCOSIS IN PRIVATE NURSERY - Peredera, R.V.; Lavrinenko, I.V.; Peredera, O.O.; Zhernosik, I.A. (World of Medicine and Biology, 2019)
The article presents epizootic data, clinical signs, pathoanatomical changes and results of laboratory tests for acute and extraordinary manifestation of dogs’ streptococcosis. Diagnosis of streptococcosis was established based on an analysis of epizootological data, clinical signs of the disease, pathological and anatomical changes, and confirmed by data from bacteriological studies. To most of the antibacterial agents studied, the isolated pathogen of streptococcus was not sensitive. The causative agent showed high sensitivity to enrofloxacin, where the growth retardation zone was 22-25 mm and tylosin (the growth retardation zone was 20-24 mm). When choosing antibacterial substances, the sensitivity to them of the pathogen of streptococcus was taken into account. "Tilozin-20" drug was applied. The drug was injected intramuscularly once a day for a dog’s daily dose of 0.5 ml per 10 kg body weight. To disinfect the premises where the puppies were kept, the "Brovades plus" disinfectant was used. The 1.0% Brudavez-Plus solution (100 ml per 10 liters of water) was used. The disinfection of the premises was carried out daily during the elimination of the outbreak.